2018
DOI: 10.1021/jacs.8b07248
|View full text |Cite
|
Sign up to set email alerts
|

Truncated Sierpiński Triangular Assembly from a Molecular Mortise–Tenon Joint

Abstract: The amalgamation of different components into a giant and intricate structure that makes quantitative and spontaneous assembly through molecular design is indispensable but challenging. To construct novel metallo-supramolecular architectures, here we present an architectural design principle based on multicomponent self-assembly. Using a carefully designed hexatopic terpyridine-based metallo-organic ligand (MOL), [RuTK], we report on the formation of supramolecular trapezoid Zn[RuTK]V, hollow hexagon Zn[RuTK]K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 76 publications
0
16
0
1
Order By: Relevance
“…Key metalloligands L1 and L2 with four uncomplexed free terpyridines are featured in a truncated rhombus bound to a V-directed tenon. They were assembled with Zn 2+ ions to introduce a discrete pinwheel-shaped star trigon P1 and pentagram P2 (the trimer and pentamer product, respectively), attributed to the intramolecular mortise–tenon joint . Both P1 and P2 were composed of rhombuses by utilizing vertex connectivity, and possess a triangle and pentagon, respectively, in the center.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Key metalloligands L1 and L2 with four uncomplexed free terpyridines are featured in a truncated rhombus bound to a V-directed tenon. They were assembled with Zn 2+ ions to introduce a discrete pinwheel-shaped star trigon P1 and pentagram P2 (the trimer and pentamer product, respectively), attributed to the intramolecular mortise–tenon joint . Both P1 and P2 were composed of rhombuses by utilizing vertex connectivity, and possess a triangle and pentagon, respectively, in the center.…”
Section: Introductionmentioning
confidence: 99%
“…They were assembled with Zn 2+ ions to introduce a discrete pinwheel-shaped star trigon P1 and pentagram P2 (the trimer and pentamer product, respectively), attributed to the intramolecular mortise−tenon joint. 27 Both P1 and P2 were composed of rhombuses by utilizing vertex connectivity, and possess a triangle and pentagon, respectively, in the center. More importantly, a larger and more complicated pinwheel-shaped hexagram P3 (a hexamer product) could be generated via the coordination of an octaterpyridine metalloligand (L3) and Zn 2+ ions (Scheme 1).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Indeed, the self-selective coordination approaches provided facile access to construction of discrete well-defined heteroleptic metallo-supramolecules through multicomponent self-assembly, producing various outputs such as prisms, trefoil knots, , molecular muscles, shuttles, and catalytic machinery. Among them, 2,2′:6′,2″-terpyridine (tpy) ligands have recently attracted considerable attention because of their adjustable coordination lability and excellent solubility to maintain homogeneity in self-assembly. , Due to the pseudo-octahedral coordination geometry of <tpy–M II –tpy>, organic molecules, such as carbazole, porphyrin, adamantane, , and crown ethers, are commonly selected as a core to create proper geometric angles. Robust <tpy–Ru II –tpy> derivatives are often functionalized to afford a variety of metalloligands in a stepwise manner, so as to suppress formation of mismatched assemblies. To lessen the synthetic burden, we have demonstrated that the tpy ligand modified by 2,6-dimethoxyphenyl substituents at 6,6″-tpy positions can spontaneously form a heteroleptic complex with an unsubstituted tpy ligand in the presence of Cd II ions . Given this molecular self-recognition, the quantitative self-assembly of a number of 2D and 3D metallo-supramolecular architectures has been successfully realized. , To further explore self-assembly behavior of the 4-fold symmetric cavitand-based tpy ligand with complementary counterparts, herein we focus our investigations on the construction of multicomponent nanocapsules bearing calix[4]­resorcinarenes.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, a variety of multivalent 2,2′:6′,2″-terpyridine (tpy)-based ligands can be obtained by palladium-catalyzed cross-coupling reactions and serve as subcomponents for self-assembly of giant metallo-supramolecules . In the supramolecular chemistry of metal–tpy complexes, a stepwise approach is commonly used to prepare predesigned metalloligands to eliminate mismatched assemblies during self-assembly. , Nevertheless, toward elevating the degree of molecular self-sorting, we have demonstrated that an equimolar mixture of 6,6″-di­(2,6-dimethoxy­phenyl)­tpy and unsubstituted tpy ligands can afford a sole heteroleptic complex upon addition of Cd II ions under ambient conditions . The complementary ligand pair offers facile access to preparation of discrete metallomacrocycles as well as metallocages via multicomponent self-assembly. , …”
Section: Introductionmentioning
confidence: 99%